Development of an Interactive PjBL-Based E-Module for Islamic Religious Education at The Junior High School Level - Ilal Fajri; Rozi Fitriza; Ahmad Sabri (Abjadia : International Journal of Education, 2026)
This study aims to develop an interactive e-module based on Project-Based Learning (PjBL) for Islamic Religious Education at the junior high school level. The study was motivated by the limited use of engaging learning media, which resulted in low student participation. This research addresses the gap by integrating PjBL syntax into a digital e-module to support meaningful and active learning, particularly in social media ethics content. This study employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 33 students (n = 33). Data were collected through observation, interviews, documentation, expert validation questionnaires, practicality questionnaires, and learning outcome tests. The effectiveness was analyzed using the Paired Sample T-Test and N-Gain score. The results showed that the e-module was highly valid (93.75%). Practicality tests indicated very practical results, with scores of 96% from teachers and 95.35% from students. The implementation of learning reached 96%, categorized as very well implemented. The effectiveness test revealed a significant difference between pretest and posttest results (Sig. < 0.05), with an N-Gain score of 79.44% (effective category). In conclusion, the developed interactive e-module based on PjBL is valid, practical, and effective for improving students’ learning outcomes.